Morpho-Histological Study of Placentae from Pregnancies Complicated by Anemia - Abeer Zubair Khan; Stuti Srivastava; Fardan Qadeer; Mahboobul Haque (Wolters Kluwer Medknow Publications, 2020)
Background: The placenta is an important organ that acts as a conduit for transporting substances from the mother to the fetus and vice versa. It performs many functions and is intimately related to both the mother and the fetus. Anemia is a leading disorder of pregnancy and is seen to effect >65% of pregnant women in India. It is also a known cause of intra-uterine growth retardation, preterm deliveries, low-birth-weight deliveries, etc. Objective: The aim is to study and compare the morphometric and histological changes seen in placentae from normal and anemic mothers. Methods: This study was done in the Department of Anatomy of Shri Ram Murti Smarak Institute of Medical Sciences and Research, Bareilly, Uttar Pradesh, India. One hundred and fifty placentae were collected, 75 each from normal and anemic mothers. A thorough morphometric and histological study of the placentae was done, and the results were recorded. Results: It was observed that the mean weight, diameter, circumference, and chorionic plate area of the placentae from anemic mothers was significantly reduced in comparison to the controls. Histological study showed that there was a significant increase in pathological changes such as syncytial knots, fibrinoid necrosis, calcification, and medial coat proliferation of blood vessels in samples obtained from placentae of anemic mothers in comparison to the controls. Conclusion: It was concluded from this study that maternal anemia has significant consequences on the developing placenta. These morphometric and microscopic changes in placental structure can in turn reduce its function, thus having an adverse effect on fetal outcome.